Differential diagnosis for whom with intellectual disability and autism spectrum disorder according to diagnostic criteria in Diagnostic and Statistical Manual of Mental Disorders (5th edition) - Ahmed, Sherif Adel Jaber; Ali, Sayed Ibrahim Ali (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the diagnosis of the difference between the intellectual disability and the autism spectrum disorder. The study sample consisted of 60 children (30 children with intellectual disability, 30 children with autism spectrum disorder). Three scales were used in this study; the measure of autism spectrum disorder for children (prepared by Gaber 2018), the measure of communication and social interaction, and the measure of the behavioral performance (prepared by the researchers of this study). The study found that there were statistically significant differences at the level of significance (0.05) among the average scores of children with intellectual disability and children with autism spectrum disorder on measurement of communication and social interaction of the three dimensions in favor of children with intellectual disability. The results of the study showed that there were statistically significant differences at the level of significance (0.05) between the average scores of children with intellectual disability and children with autism spectrum disorder on the measure of behavioral performance in its four dimensions in favor of children with intellectual disability.
Keywords: differential diagnosis; intelligence deficit; autism spectrum disorder